Code-Switching Functions in Modern Hebrew Teaching and Learning. Issue 4 (1st October 2016) - Gilead, Yona
ABSTRACT: The teaching and learning of Modern Hebrew outside of Israel is essential to Jewish education and identity. One of the most contested issues in Modern Hebrew pedagogy is the use of code-switching between Modern Hebrew and learners' first language. Moreover, this is one of the longest running disputes in the broader field of second language research and education. Based on recent conceptualizations of bi/multilingualism together with findings from an empirical investigation of beginner students at an Australian university, this article argues that strategic use of code-switching serves the needs of both learners and teachers working within a bi/multilingual educational environment.